Performance of carrot (Daucus carota) under different WSF concentrations and frequency of foliar fertilization in aridisols of western Rajasthan - Rakesh Chouhan; Santosh Choudhary; S. K. Moond; Ummed Singh; Suman Poonia (Annals of Agricultural Research, 2023)
A field experiment was conducted at the College of Agriculture, Jodhpur during Rabi 2020, to assess the effect of foliar fertilization of NPK water soluble fertilizer on carrot. The treatments comprised five spray concentrations of water-soluble fertilizers (WSF) including control and two spray frequencies allocated in a factorial randomized block design with three replications. The results revealed that among the spray concentrations, WSF 2.0% being at par with WSF 1.5% recorded significantly higher foliage length, number of leaves/ plant, fresh weight of aerial parts, root diameter, core diameter, root length, root weight, root yield (25.1 t/ha), carotene, net returns (`1,67,279/ha) and B:C ratio (1.84) as compared to WSF 0.5 % and control. Further, four sprays recorded significantly higher foliage length, number of leaves per plant, fresh weight of aerial parts, root diameter, core diameter, root length, root weight, root yield (24.2 t/ha), TSS, net returns (`1,54,491/ha) and B:C ratio (1.70) over two sprays. Hence, spray concentration of WSF 2.0% with four sprays on carrot was found optimum to produce higher yield, quality and monetary returns of carrot in arid western Rajasthan.